PARTISIPASI MASYARAKAT DALAM KEGIATAN REHABILITASI HUTAN DAN LAHAN (RHL) DI KABUPATEN BONE BOLANGO - Novi Purwanti; Sukirman Rahim; Marini S Hamidun (Jurnal Belantara, 2022)
This study aims to know; (1) community participation in forest and land rehabilitation activities in Meranti Village, Tapa Sub-district, Bone Bolango District, (2) strategy for increasing community participation in forest and land rehabilitation activities in Meranti Village, Tapa Sub-district, Bone Bolango District. This study uses a quantitative approach with descriptive and inferential methods. The data in this study are primary data from the distribution of questionnaires. The data analysis technique uses descriptive and SWOT analysis. The findings show that: (1) The achievement score for the community participation variable in forest and land rehabilitation activities is 79.69% which is in the fairly good category. The results of each indicator show that the voice and control indicators are in the fairly good category, while the access indicator is in a good category. (2) The strategy for increasing community participation in forest and land rehabilitation activities is in quadrant 3 of what is called the Turn Around strategy. This strategy emphasizes the utilization of various opportunities to change the weaknesses of the community in optimizing its role in environmental conservation activities that can be carried out by the government with 2 main steps, including strengthening the capacity of the community overall and government cooperation with various parties related to the environment.